1976
DOI: 10.1038/bjc.1976.125
|View full text |Cite
|
Sign up to set email alerts
|

Geographic correlation between mortality from primary hepatic carcinoma and prevalence of hepatitis B surface antigen in Greece

Abstract: Summary.-Average annual age-adjusted mortality rates per 100,000 from primary hepatic carcinoma (PHC) among males for [1971][1972][1973]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
6

Year Published

1979
1979
1985
1985

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
(17 reference statements)
0
9
0
6
Order By: Relevance
“…The numerous case-control studies that indicated a causative role for HBV infection in the development of HCC (Tabor et al, 1977;Maupas et al, 1977;Kubo et al, 1977;Johnson et al, 1978;Trichopoulos et al, 1978;Kew et al, 1979;Omata et al, 1979) have been followed by evidence that suggests that chronic active infection with HBV may be a necessary initial factor in the development of all cases of HCC. A prospective study in Taiwan has indicated a relative risk of over 200 with all but one case occurring among persons who were carriers prior to development of HCC (Beasley et al, 1981) while viral DNA has been found incorporated into the host genome of HCC patients (Shafritz et al, 1981) including those who have no viral markers of HBV infection (Brechot et al, 1982). 1t has also been suggested that chronic HBV infection acting alone could be responsible for the large range of incidence for HCC that exists between different countries and that aflatoxin has little carcinogenic effect on humans (Prince, 1978;Lutwick, 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerous case-control studies that indicated a causative role for HBV infection in the development of HCC (Tabor et al, 1977;Maupas et al, 1977;Kubo et al, 1977;Johnson et al, 1978;Trichopoulos et al, 1978;Kew et al, 1979;Omata et al, 1979) have been followed by evidence that suggests that chronic active infection with HBV may be a necessary initial factor in the development of all cases of HCC. A prospective study in Taiwan has indicated a relative risk of over 200 with all but one case occurring among persons who were carriers prior to development of HCC (Beasley et al, 1981) while viral DNA has been found incorporated into the host genome of HCC patients (Shafritz et al, 1981) including those who have no viral markers of HBV infection (Brechot et al, 1982). 1t has also been suggested that chronic HBV infection acting alone could be responsible for the large range of incidence for HCC that exists between different countries and that aflatoxin has little carcinogenic effect on humans (Prince, 1978;Lutwick, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, higher prevalence of HbsAg have been reported from Taiwan both in control populations and among HCC patients (Tong et al, 1971;Sung et al, 1980) than have been found in Mozambique (Bersohn et al, 1974;Kew et al, 1979) and yet the age-standardised incidence for HCC is lower in Taiwan (calculations from data given in Beasley et al, 1981) than in Mozambique. The one clear indication of a geographical association comes from Greece, an area of moderate incidence for HCC, where mortality rates from HCC in different regions showed a correlation with the proportion of army recruits who were positive for HBsAg in both rural and urban areas (Trichopoulos et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relatively high proportion of HBs antigen-negative patients with liver cirrhosis with hepatocellular cancer in the United States (Dourdourekas et al, 1975) and Great Britain (Fisher et al, 1976), the direct or indirect oncogenic role of ethanol in liver cirrhosis is widely underestimated. The reason may be the fact that all published studies have been carried out in West, East, or South Africa or in the Far East, areas with a known high prevalence of HBs antigen; in these studies a close relationship between the incidence of primary liver cell carcinoma with and without liver cirrhosis on the one hand and HBs antigen on the other hand has been demonstrated (Moertel et al, 1970;Sherlock et al, 1970;Vogel et al, 1970;Tong et al, 1971;Simons et al, 1972;Kew et al, 1974;Prince et al, 1975;Williams, 1975;Trichopoulos et al, 1976;Kubo et al, 1977aKubo et al, , 1977b.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown a highly significant excess of surface antigen, surface antibody, and core antibody in these patients (e.g., see Sherlock et al, 1970;Reed et al, 1973;Nishioka et al, 1975;Prince et al, 1975;Maupas et al, 1975;Larouze et al, 1976;Trichopoulos et al, 1976;Nazarewicz et al, 1977;Tabor et al, 1977).…”
Section: [1o7]mentioning
confidence: 99%